A inserção da fenomenologia na formação em psicologia da Pontifícia Universidade Católica de São Paulo: um olhar para os seus participantes - Perosa, João Pedro Benzaquen (2019)
The bachelor course in Psychology at Pontifical Catholic University of São Paulo is one of the oldest and most recognized in Brazil and Latin America, as it has contributed to the advance of research, teaching techniques and service to the Psychology world. The introduction of Phenomenology in the Psychology graduation course at PUCSP is part of the history of Psychology as a science and a profession. This research studied the period since 1964, when Phenomenology was introduced as a subject in the Psychology HistoryChair, to when it became an exclusive chair of Phenomenological Psychology. Phenomenology was introduced in the Psychology graduation course at PUCSP by the hiring of the Portuguese philosopher Maria Fernanda Seixas Farinha Beirão in 1964. Her contributions allowed for the constitution of a group of psychologists and students that worked for the creation of a Phenomenological Psychology, that today expands its methods to diverse Psychology areas as Psychotherapy, Educational Psychology and Political Psychology. This research includes the interview of seven partners during this period, and that were teachers at this University. The reflexive interview technique was used, which helps to create complex testimonials of this data perspective. All these interviews were transcribed, returned to the research participants, discussed and approved by them. The method of analysis was founded in the meaning constellation as proposed by Heloisa Szymanski, that allows for the perception of important aspects of this historical experience. The first constellation was ‘Between the Clinic and the Philosophy’, which showed the epistemological emphasis and the clinical foundation of this process. The second was: ‘A Third Path’, that presented the critical posture of the Phenomenology to the hegemonic Psychology school at that moment. The third constellation was ‘The Maria Fernanda Seixas Farinha Beirão Presence’, which testifies to the importance of this professor as a pioneer in the teaching, research and development of this phenomenological method in Psychology. From the optics of these constellations this research understood that this process is part of the Psychology history development, which incorporates the Phenomenology as a Philosophy method, as well as how the American Humanist Psychology and the German and French Existential Psychology influence it. It also allowed to verify aspects from the PUCSP institution history that influenced the introduction of Phenomenology as a valid approach in Psychology. This research scaled new studies opportunities that will help to better understand the development of the Phenomenology and its influence in Psychology, and also discussed a descriptive and hermeneutic method of research to Psychology History